2015
DOI: 10.1177/2158244015580378
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Model for Physical Activity, Healthy Eating, Alcohol Drinking, and Risky Driving Among Albanian Youth

Abstract: Studies report an increasing prevalence of health risk behaviors among Albanian adolescents and young adults. The ProblemBehavior Theory provides a useful framework for explaining both health-compromising and health-enhancing behaviors by considering several personal and environmental factors. The present study used a model with seven independent variables including age, gender, attitudes, locus of control, risk behavior tendency, stress, and parent/peer models of health behavior to predict two health-compromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(58 reference statements)
0
2
0
1
Order By: Relevance
“…Psychological factors include sociodemographic, familiar and sociocognitive determinants such as professional occupation, education level, age, race/ethnicity, economic status, self-perception body image, self-perceived health status and so on. 4 5 9–12 Professional occupation is considered a factor of influence over an individual’s health and lifestyle. 10 Similarly, voluntary retirement has been shown to be beneficial to health and health behaviours, especially recreational physical activity 13 14 and moderate alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological factors include sociodemographic, familiar and sociocognitive determinants such as professional occupation, education level, age, race/ethnicity, economic status, self-perception body image, self-perceived health status and so on. 4 5 9–12 Professional occupation is considered a factor of influence over an individual’s health and lifestyle. 10 Similarly, voluntary retirement has been shown to be beneficial to health and health behaviours, especially recreational physical activity 13 14 and moderate alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The most common cause of distraction in risky driving is practicing a secondary activity while driving, and about 11% of fatal traffic accidents were related to distracted driving behavior (Qin et al, 2019). A study conducted among Albanian youth found that 72.4% of participants aged 18-22 reported engaging in risky driving behavior (Melonashi and Shkembi, 2015). Youth has a higher tendency to use mobile phones while driving and not wearing seatbelts (Ramisetty-Mikler and Almakadma, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Em razão desses elementos e considerando que a sociabilização dos homens gera uma ampla gama de problemas de saúde, são necessárias soluções por meio de políticas públicas, programas e serviços de saúde que ponderem os aspectos particulares desse público. E nesse sentido, é importante salientar que quando se existe apoio emocional e incentivos saudáveis do seu grupo de referência, os homens podem ser in uenciados positivamente (WILSON-SALANDY;NIES, 2012;NGUYEN-MICHEL et al, 2006;MELONASHI;SHKEMBI, 2015;STULTS-KOLEHMAINEN;SINHA, 2014;MACHADO et al, 2007).…”
Section: Introductionunclassified